Studies on the genus Aporcelaimellus Heyns, 1965 (Nematoda, Dorylaimida, Aporcelaimidae). Four new species with complex uterus from Southeastern Iberian Peninsula - Álvarez-Ortega, Sergio; Abolafia, Joaquín; Liébanas, Gracia; Peña-Santiago, Reyes (Zootaxa, 2012)
Four new species with complex uterus of the genus Aporcelaimellus, collected mainly in natural areas in the IberianPeninsula, are identified and described here. Aporcelaimellus alpujarrensis sp. n. is characterized by having body1.72–1.91 mm long, lip region offset by constriction and 14–15μm broad, odontostyle 14–16μm long with apertureoccupying 67–70% its length, neck about 455μm long, pharyngeal expansion about 224μm long, uterus tripartite and145–206μm long, V = 53–55, tail convex conoid (27–34μm, c = 55–71, c’ = 0.9–1.1), spicules 56–60μm long, and 7–9irregularly spaced ventromedian supplements with hiatus. Aporcelaimellus castaneanus sp. n. is characterized by havingbody 2.18–2.83 mm long, lip region offset by constriction and 20–23μm broad, odontostyle 22–24μm long with apertureoccupying 62–67% its length, neck 581–662μm long, pharyngeal expansion 300–355μm long, uterus tripartite and164–348μm long, V = 52–58, tail conical with rounded terminus (44–52μm, c = 48–60, c’ = 0.8–1.1), spicules 94–103μm long, and 14–15 irregularly spaced ventromedian supplements which lack hiatus. Aporcelaimellus communis sp. n. ischaracterized by having body 2.56–4.22 mm long, lip region offset by constriction and 19–25μm broad, odontostyle19–26μm long with aperture occupying 64–74% its length, neck 595–750μm long, pharyngeal expansion 321–427μmlong, uterus bipartite and 190–450μm long, V = 51–60, tail short and convex conoid (29–50μm, c = 63–109, c’ = 0.5–1.0),spicules 89–118μm long, and 16–25 irregularly spaced ventromedian supplements with hiatus. Aporcelaimellus tenuis sp.n. is characterized by having body 1.89–2.70 mm long and comparatively slender (a = 35–49), lip region offset byconstriction and 15–18μm broad, odontostyle 15–21μm long with aperture occupying 60–70% of its length, neck488–645μm long, pharyngeal expansion 251–366μm long, uterus bipartite and 135–213μm long, V = 55–58, tail convexconoid with rounded terminus (25–40μm, c = 64–92, c’ = 0.8–1.1), spicules 52–66μm long, and 11–12 irregularly spaced SEM pictures, are given for the four species.ventromedian supplements with hiatus. Measurements and illustrations, including line drawings, LM pictures and and/or